Chapter 4 A Receiver Approach to Governance in Family Firms: The Role of Justice Perceptions - Isabel C. Botero; Tomasz A. Fediuk (Emerald Publishing Limited, 2023)
Justice perceptions describe an individual's evaluation of whether decisions or actions are fair or unfair. These perceptions are important because they affect individual attitudes and behaviors in different situations. Family firms develop and implement governance policies and structures (i.e., governance systems) to diminish the problems that can arise from the overlap between the business, the family, and the ownership systems of a firm. Governance systems help family firms have a clear structure of accountability and a clear understanding of the rights and responsibilities that family and non-family members have toward the family enterprise. Research on governance to date has focused on the practices and policies that exist and their effects on the family firm. However, in the governance context, individual perceptions are important because they are likely to affect the attitudes that family and other members have toward the family enterprise and the likelihood that they will follow the different policies when they are implemented. This chapter takes a receiver perspective to explain how individuals create justice perceptions based on governance mechanisms and the effects of these perceptions. The goal is to understand how we can use this information when developing governance practices in family firms.
10.1108/978-1-83797-200-520231004; 10.1108/978-1-83797-200-520231004; Family Firms and Family Constitution; EBP099697173